STRATEGIES FOR IMPROVING EMPLOYEE PERFORMANCE THROUGH STRENGTHENING ORGANIZATIONAL CULTURE, TRANSFORMATIONAL LEADERSHIP AND WORK MOTIVATION - Wahyu Wiguna; Nancy Yusnita; Widodo Sunaryo (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to find strategies and ways to improve the performance of permanent employees at the operator level at the Association of Temporary Storage and Tank Terminal Entrepreneurs (APT3B) of Banten Province. The population in this study were permanent employees at the operator level, with a total of 234 respondents selected using the Multistage Random Sampling method. This study uses a mix method approach, combining quantitative and qualitative methods to analyze the factors that influence the performance of permanent employees at the operator level at APT3B Banten Province. The study population consisted of 234 employees selected using Multistage Random Sampling. Quantitative data were collected through questionnaires and analyzed using path analysis. The qualitative approach was carried out through in-depth interviews with a number of employees and analyzed using thematic analysis. The combination of these two approaches is expected to provide a comprehensive understanding of the influence of organizational culture, transformational leadership, and work motivation on employee performance. Based on the results of the study, organizational culture, transformational leadership, and work motivation have a significant positive effect on employee performance at APT3B. Organizational culture and transformational leadership have a greater direct influence on employee performance, while work motivation acts as an intervening variable with a smaller influence. Strengthening organizational culture and transformational leadership can improve overall employee performance and motivation and support the achievement of organizational goals. This study supports previous findings and provides direction for improving human resource management at APT3B.